2013
DOI: 10.1002/cbdv.201300060
|View full text |Cite
|
Sign up to set email alerts
|

From Dioxygen Storing to Dioxygen Sensing with Neuroglobins: An Insight from Molecular Mechanics

Abstract: This work deals with two neuroglobins from phylogenetically distant organisms. Deriving from the acoelomorph Symsagittifera roscoffensis, SrNgb is functionally pentacoordinated, and is assumed to function as a reserve of dioxygen (O₂). Obtained from mice, mNgb is functionally hexacoordinated, and presumably triggers signals from sensing O₂. Here, it is investigated how these two globins are permeated by diatomic gases, SrNgb by O₂ and mNgb by CO. With protein atomic coordinates available from high-resolution X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This is not a characteristic of all protein–gas systems that I have investigated. Out of these, referred to at section above, it was only with myoglobin , cytoglobin , Symsagittifera roscoffiensis neuroglobin , and heme oxygenase OH‐1 , that the shortest pathway between the active center and the bulk solvent was preferred. For these, we speculated that rapid supply of O 2 along the shortest pathway reflects the urgent cellular need of O 2 , which led to the evolution of ad hoc O 2 carriers, sensors, and enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a characteristic of all protein–gas systems that I have investigated. Out of these, referred to at section above, it was only with myoglobin , cytoglobin , Symsagittifera roscoffiensis neuroglobin , and heme oxygenase OH‐1 , that the shortest pathway between the active center and the bulk solvent was preferred. For these, we speculated that rapid supply of O 2 along the shortest pathway reflects the urgent cellular need of O 2 , which led to the evolution of ad hoc O 2 carriers, sensors, and enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, we have also investigated by MD the permeation by O 2 of other proteins, including O 2 ‐sensors , oxygenases , oxidases , oxidoreductases , and singlet dioxygen generators . None of these proteins has the special features of UOX, with the active center at the interface between two subunits, thus likely requiring the intact homotetramer for functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Present study of AXCPÀNO complexes has been carried out along RAMD simulations [13], as in previous examples of permeation of proteins by biologically relevant gases, concerning myoglobin [14], H-NOX [15], lipoxygenases [16], MauG [17], cytoglobin [18], heme oxygenase [19], and neuroglobins [20]. With RAMD simulations [13], a randomly oriented tiny force is applied to the center of mass of the ligand.…”
Section: Basis and Scope Of Present Workmentioning
confidence: 99%
“…Many of them displayed novel characteristics not seen in the classical globins like myoglobin (Mb). A literature search revealed that folding and stability of Hbs were not investigated for diverse globins (15,16). Most of the contributions relate to Mb and human Hb (17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%